2018
DOI: 10.1111/agec.12446
|View full text |Cite
|
Sign up to set email alerts
|

Health and hunger: nutrient response to income depending on caloric availability in Nepal

Abstract: Using data from NLSS III, we estimate nutrient-income elasticities for macronutrients, vitamins, and minerals. We further allow for differential nutrient demand response to income depending on where a household is in the caloric availability distribution. We find that some nutrients are income inelastic indicating that they are necessity goods while others are relatively income elastic. We further test and reject equivalent nutrientincome elasticities across the caloric availability distribution. Households in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…This accords with other studies from developing countries showing that increases in income raise consumption of nutritious foods and important micronutrients(Ali et al, 2018;Chaijaroen, 2019;Cornia, 1994;Currie, 2009;Hoang, 2018; R. T Jensen & Richter, 2004;Steckel, 1995),. and can increase other investments in children(Evans et al, 2019a;Ferreira & Schady, 2009;R.…”
supporting
confidence: 89%
“…This accords with other studies from developing countries showing that increases in income raise consumption of nutritious foods and important micronutrients(Ali et al, 2018;Chaijaroen, 2019;Cornia, 1994;Currie, 2009;Hoang, 2018; R. T Jensen & Richter, 2004;Steckel, 1995),. and can increase other investments in children(Evans et al, 2019a;Ferreira & Schady, 2009;R.…”
supporting
confidence: 89%
“…For NSA projects to be effective, integration with other interventions aimed at improving livelihood and income opportunities for the very poor should be envisaged [ 68 ]. Furthermore, as Ali et al [ 69 ] reported, using data from Nepal, growth policies that improve the income of the very poor and protect them from income shocks would be likely to result in nutritional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike red meat, white meat and dairy products are more preferrable for 26.56% of the respondents, with 25.94% claiming they are more willing to change their consumption of white meat and milk rather than change the consumption of red meat (see Figure 4). As far as the decision (see Ali et al, 2018) regarding a good knowledge on a product is concerned, in the respondents' opinion this is an untapped option. In other words, 70.31% consider that nutritional information on the label is not a decision-making factor in the purchasing process.…”
Section: Resultsmentioning
confidence: 99%